Transcriptional activation in Drosophila spermatogenesis involves the mutually dependent function of aly and a novel meiotic arrest gene cookie monster. - Jiang, J.; White-Cooper, H. (Development, 2003)
In Drosophila spermatogenesis, meiotic cell cycle progression and cellular differentiation are linked by the function of the meiotic arrest genes. The meiotic arrest genes control differentiation by regulating the transcriptional activation of many differentiation-specific genes. The meiotic arrest genes have been subdivided into aly and can classes, based on the mechanism by which they control cell cycle progression. aly has previously been shown to encode a chromatin-associated protein. We present the identification, cloning and characterisation of a novel Drosophila meiotic arrest gene, cookie monster (comr), that has a mutant phenotype indistinguishable from that of aly. A null mutant allele of comr is viable but male sterile. Mutant primary spermatocytes fail to initiate transcription of a large number of genes, and arrest before entry into the meiotic divisions. In adult males, expression of comr is testis specific, low levels of transcripts are detected at other stages of development. comr encodes a novel acidic protein, which is nuclear and primarily localised to regions of chromatin in primary spermatocytes. The nuclear localisation of Aly and Comr proteins are mutually dependent. Finally, we show that active RNA polymerase II is found in distinct domains in the nucleus that constitute a subset of the total Comr stained chromatin.